Mediating effect of coping style between empathy and burnout among Chinese nurses working in medical and surgical wards - Li Cheng; Jiao Yang; Mengyuan Li; Wenru Wang (Wiley, 2020)
Abstract Aim This study aimed to investigate burnout, coping style and empathy among Chinese nurses working in medical and surgical wards and to examine the mediating effect of coping style between empathy and burnout among this group of nurses. Design A cross‐sectional questionnaire survey. Method The study recruited a convenience sample of 363 nurses from three university‐affiliated tertiary hospitals in Shiyan City, Hubei, China. A set of self‐administered questionnaires was used to measure the variables of burnout, coping style and empathy. Structural equation modelling was performed using AMOS 20.0. Results Nurse burnout was prevalent among Chinese nurses in medical and surgical wards, and coping style and empathy were significantly associated with burnout. Positive coping strategies and high levels of empathy could reduce burnout in nurses. Coping strategies were found to play a partial mediating role between empathy and burnout among this group of nurses.